Exploring Muhammadiyah Generation Z Perpectives Toward Halal Cosmetics - Alfina Rahmatia; Mufti Alam Adha; Sisilia Puspita Anggraeni; Annisa Millania (Agregat: Jurnal Ekonomi dan Bisnis, 2022)
Nowadays, halal cosmetic gets popular among young generation, especially generation Z as an internet generation. It made Indonesia as the second largest expenditure on halal cosmetic in the world on 2017 in which the Muslim generation Z becomes the market target. Owing to such interests, the main objective of this study is to explore the perspectives of Muhammadiyah generation z toward halal cosmetics in Indonesia. The study uses qualitative methode through literature study and in-depth interview with convenience sampling method in which the interview data use Nvivo 12 application and descriptive analysis. The result from literature study based on Nvivo 12 analysis shows that religiosity value, health factor, and halal cosmetics marketing strategy are playing a role to the perspectives of Muslim generation Z toward halal cosmetics.